Alternative Assessment Forms for Foreign Language Classrooms - AKNOUCH, LAYLA (International Journal of Language and Literary Studies, 2023)
Research in the field of foreign language teaching and learning has proved that testing as an assessment instrument is not an adequate means of assessing the multiple dimensions of language learning. As a result, various alternative assessment forms have been suggested in the literature to compensate for the weaknesses and limitations of conventional testing and ensure more effective learning. Accordingly, this paper seeks to review the literature on the different forms of alternative assessment that language teachers could use in addition to traditional assessment. More specifically, the present paper aims to explore the types of alternative assessments, stresses their importance by listing the many benefits that these assessment methods proved to have, and also discusses some of their perceived limitations.